Impact of household demographic characteristics on energy conservation and carbon dioxide emission: Case from Mahabad city, Iran. (1st March 2020) - Soltani, Mohammad; Rahmani, Omeid; Ghasimi, Dara S.M.; Ghaderpour, Yousef; Pour, Amin Beiranvand; Misnan, Siti Hajar; Ngah, Ibrahim
Abstract: This study explores the impact of different household demographic characteristics on energy conservation and carbon dioxide (CO2 ) emission in Mahabad city located in the northwest of Iran. The structural model adopted was composed of six variables, including household age, household size, educational qualification, income quintile, gender, and energy conservation concerning demographic characteristics and energy sources and consumptions. To compare predictability power of effects of these variables concerning households' energy conservation and CO2 emissions, a crisp instruction on how to evolve a statistical technique for analyzing data was provided by partial least squares structural equation modeling (PLS-SEM). To verify the reliability of the PLS-SEM technique, the statistical significance test was performed by investigating path coefficients. The study revealed that households consume approximately 89.71% on liquefied petroleum gas (LPG), 9.87% on electricity while the rest 0.43% on kerosene, petrol, and diesel monthly. Eventually, the results of this study showed that household age, household size, and carbon dioxide emissions, except education background and income level, are significantly correlated with energy conservation. Highlights: Income level is the most crucial factor that causes carbon emission inequality. Demographic feature of household age impacted households' energy conservation. The amount of carbon emissions is influenced by aging in households. CO2 emissions of families change considerably as the household's position changes.